A Study on the Ability of Supra-Segmental and Segmental Aspects in English Pronunciation - Febronia Lasi (Universitas Cokroaminoto Palopo, 2020)
This study attempted to examine the EFL students’ Basic English Pronunciation (BEP) at the first semester of the English study program, the State University of Timor. It was aimed at finding out the mastery of the students’ ability towards the Basic English Pronunciation (BEP), to what extent do the students still find difficulties to pronounce the basic English words, and to what level do the students' mastery level of pronunciation categorized? The method applied in this research was a descriptive quantitative method that employed the syntax of mathematical operation to investigate the properties of data collection (Walliman, 2005). The instrument was a list of 24 numbers of groups of Voice Consonants and Unvoiced Consonants of Basic English Pronunciation taken from “Improve Your English Pronunciation and Learn over 500 Commonly Mispronounced Words”, meanwhile, 26 students were chosen from the freshmen students of English Study Program (ESP) to be the subject of this present study. The result showed that the students’ ability in pronouncing the Basic English words was fair. Particularly, the students mostly had the ‘Enough’ level of ability at the four elements of supra-segmental as such: stress, intonation, voice quality and gesture. Specifically, at this ‘Enough level’, there were 16 students (61.5%) of ‘Stress’ element, 17 students (65.3%) of ‘Intonation’ element, 13 students (50.0%) of ‘Voice Quality’ and ‘Gestures’ as part of Segmental element was 16 students (61.5%). Meanwhile, at the ‘Rhythm’ element, most students (53.8% = 14 students) showed the ‘Less’ ability in this element and only 12 (46.1%) categorized at the level of ‘Enough’’. Otherwise, there were no students in the ‘Bad’ level category. However, few students still encountered difficulties in Segmental element (Voice Quality) and Supra-segmental parts such as words’ stressing, intonation, rhythm, and gestures respectively.